FDA-approved drugs that interfere with laboratory tests: A systematic search of US drug labels. (2nd January 2017) - Yao, Hui; Rayburn, Elizabeth R.; Shi, Qiang; Gao, Liang; Hu, Wenjie; Li, Haibo
Abstract: Drug-related laboratory test interference or drug/laboratory test interactions (DLTI) are a major source of laboratory errors. DLTI is of concern with regard to both the clinical diagnosis and the monitoring of patients. Although there have been numerous reports about specific drugs that interfere with laboratory tests, there has not been a recent review on the topic. We herein provide a review of the known DLTI of US FDA-approved drugs based on a systematic search of DailyMed, a website containing the labels of US FDA-approved drugs. The labels for all human single-ingredient prescription drugs included in the database (1368) were searched using stemmed keywords and were manually reviewed for their relevance to DLTI. A total of 134 labels were positive, which indicated that the drug interferes with at least one clinical laboratory test. Antibacterial agents, psychotropic drugs and contrast media are the classes of drugs most likely to lead to DLTI. Urine was the clinical sample most frequently affected by DLTI. The FDA drug label is a source of information for studies of DLTI, although information is still lacking for most drugs, and additional improvements are needed for many of the existing records. Medical professionals, clinicians and laboratory staff should keep these possible interactions in mind when interpreting the results of laboratory tests, and should ensure that they obtain a complete and accurate record of all drugs being used by patients in order to anticipate potential DLTI. The development of a reporting system to address potential DLTI is warranted.